IMPLEMENTASI PENDEKATAN TAKTIS TERHADAP MOTIVASI DAN KETERAMPILAN BERMAIN SISWA DALAM PEMBELAJARAN EKSTRAKURIKULER FUTSAL - Reza Rusdyana, - (2023)
Implementation of the appropriate approach can have an impact on optimal futsal game performance as well as on the motivation of the students themselves. The purpose of this study was to determine the effect of the tactical approach on students' futsal game performance skills and the effect of the tactical approach on student motivation. The method used in this research is quasi experiment with one group pretest-posttes design. In sampling using simple random sampling technique, namely randomly selecting students who take part in extracurricular futsal, totaling 28 students. The instrument uses the Games Performance Assesment Instrument (GPAI) which measures student game performance including decision making (DM), skill excecution (SE), and supporting (Sup), and the Sport Motivation Scale-II (SMS-II) to measure motivation to play futsal. The population in this study were all students who participated in extracurricular futsal at Kutawaringin 1 Junior High School, totaling 30 people with a sample of 28 people. Data analysis in this study used a prerequisite test, namely the Shapiro-Wilk test, then the t test using the Paired Sample T-Test test and the N-Gain Score test to determine the effectiveness of the tactical approach with the help of the SPSS 25 application. Based on data processing and analysis, it was found that there was a significant effect of the tactical approach on playing skills and student motivation. Thus it can be concluded that through the tactical approach provides a significant influence on student motivation and game performance.